Evidence of Magnon-Mediated Orbital Magnetism in a Quasi-2D Topological Magnon Insulator - Alahmed, Laith; Zhang, Xiaoqian; Wen, Jiajia; Xiong, Yuzan; Li, Yi; Zhang, Li-Chuan; Lux, Fabian; Freimuth, Frank; Mahdi, Muntasir; Mokrousov, Yuriy; Novosad, Valentine; Kwok, Wai-Kwong; et al. (Nano Letters, 2022)
We explore spin dynamics in Cu(1,3-bdc), a quasi-2D topological magnon insulator. The results show that the thermal evolution of the Landé g factor (g) is anisotropic: gin-plane decreases while gout-of-plane increases with increasing temperature T. Moreover, the anisotropy of the g factor (Δg) and the anisotropy of saturation magnetization (ΔMs) are correlated below 4 K, but they diverge above 4 K. We show that the electronic orbital moment contributes to the g anisotropy at lower T, while the topological orbital moment induced by thermally excited spin chirality dictates the g anisotropy at higher T. Our work suggests an interplay among topology, spin chirality, and orbital magnetism in Cu(1,3-bdc).
CRIS-Team Scopus Importer:2023-03-27
Keywords: g factor anisotropy; kagome magnet; magnon excitation; topological magnon insulator; topological orbital moment